Exploring the Impact of COVID-19 Restrictions on Nursing Home Residents', Families', and Staff's Perceptions of Bioethical Principles: A Qualitative Study - Ge, Yimin; Xu, Shengjia; Capron, Alexander M; Keller, Michelle S; Hlávka, Jakub P (Journal of applied gerontology, 2024)
In this study, we employed a pre-interview survey and conducted interviews with nursing home staff members and residents/family members to understand their perceptions of whether the COVID-19 restrictions fulfilled obligations to nursing home residents under various principles, including autonomy, beneficence, nonmaleficence, justice, and privacy. We conducted 20 semi-structured interviews with staff members from 14 facilities, and 20 with residents and/or family members from 13 facilities. We used a qualitative descriptive study design and thematic analysis methodology to analyze the interviews. Findings from the pre-interview survey indicated that, compared to nursing home staff, residents and their families perceived lower adherence to bioethics principles during the pandemic. Qualitative analysis themes included specific restrictions, challenges, facility notifications, consequences, communication, and relationships between staff and residents/family members. Our study exposes the struggle to balance infection control with respecting bioethical principles in nursing homes, suggesting avenues for improving processes and policies during public health emergencies.
Keywords: rozhovory jako téma; dospělí; kontrola infekce; Qualitative Research; Female; Interviews as Topic; policy; SARS-CoV-2; rodina; postoj zdravotnického personálu; Adult; bioethics; ženské pohlaví; lidé; Homes for the Aged; COVID-19; domovy pro seniory; Attitude of Health Personnel; Nursing Homes; bioetická témata; Bioethical Issues; Male; Aged; nursing homes; Family; Infection Control; lidé středního věku; senioři; mužské pohlaví; qualitative methods; Middle Aged; long-term services and supports; kvalitativní výzkum; pečovatelské domovy; Humans